Numerical simulation of landslide motion based on thermo-plastic mechanics. (10th November 2020) - Wang, Zhongfu; Liu, Wei; Li, Dongdong; Dai, Zhiqing
Landslides with long run-out and high velocities pose severe threat to infrastructures and lives in mountain areas. Frictional heating has long been considered a mechanism responsible for some remarkable characteristics of natural landslides such as surprisingly long travel distances and high velocities. In order to study the influence of this mechanism on the motion of such landslides, one method considering the thermo-plastic mechanics was combined with a depth-averaged model for simulating the long run-out motion of landslides in the condition of deformation. The effects of several key parameters on thermo-plastic mechanics were discussed by several numerical tests through the processes of landslide motion, heat production and diffusion, pore-fluid pressure generation and dissipation, and thermo-plastic collapse of the soil skeleton at the shear zone. Then the effectiveness of the model was verified by comparing the numerical results with the field investigation of Sanxicun landslides.